دور المراجعة الداخلية في تحقيق الريادة البيئية المستدامة في بيئة الأعمال: دراسة تطبيقية على بعض شركات الأسمنت - السيد، سهام سيد محمد (جامعة المنوفية - كلية التجارة, 2022)
هدفت الدراسة إلى تحديد دور نشاط المراجعة الداخلية المضيف للقيمة في تحقيق الريادة المستدامة في بيئة الأعمال بالتطبيق علي بعض شركات الأسمنت، وتوضيح أهمية المراجعة الداخلية مصدرا قيما لبيئة الأعمال في تحقيق جودة الأداء البيئي ويمكن أن تعزز الريادة البيئية المستدامة والأداء الكلى للمنظمة علي تحقيق الريادة البيئية المستدامة في بيئة الأعمال لهذا القطاع حتي يمكن أن يحقق النمو والاستمرار في الأسواق، وذلك من خلال دور المراجعة الداخلية في تحقيق الريادة البيئية المستدامة في بيئة الأعمال بالتطبيق علي بعض شركات الأسمنت، مع الإشارة إلى أهم المشاكل التي تواجه هذا القطاع الهام والتي تتمثل في دور المراجعة الداخلية في مواجهة الممارسات والأنشطة لتفعيل دورها في تحسين جودة الأداء البيئي ومن ثم تحقيق ريادة الأعمال البيئية، وعلي سبيل ذلك قامت الباحثة بتوزيع استمارة استقصاء شملت متغيرات الدراسة، واستخدمت الباحثة هذه الاستمارة كأداة لجمع البيانات من مجتمع الدراسة، والذي بلغ حجم عينته من (٣٨٥) مفردة من العاملين والمرجعين الداخليين، ومراقبي الحسابات بنفس الشركات. توصلت الدراسة إلى أن عبارات المتغير المستقل"، دور المراجعة الداخلية"، لدي العاملين بالشركة كانت بدرجة متوسطة، وكان ترتيب أبعاد استمارة الاستقصاء من حيث المتغير التابع "الريادة البيئية المستدامة"، بدرجة توافر متوسط، وأكدت نتائج الدراسة وجود علاقة ارتباط طردية بين دور المراجعة الداخلية لدي العاملين بالشركة والمراجعين وتحقيق الريادة البيئية المستدامة من وجهه نظرهم، وأوصت الدراسة بضرورة حرص المنشآت على تنظم فعاليات تثقيفية والاهتمام بإنشاء مراكز متخصصة في ريادة الأعمال. The study aimed to determine the role of the value-adding internal audit activity in achieving sustainable leadership in the business environment - on some cement companies, and explain the importance of internal auditing as a valuable source for the business environment In achieving quality environmental performance, it can enhance sustainable environmental leadership and the overall performance of the organization to achieve sustainable environmental leadership in the business environment of this sector In order to achieve growth and continuity in the markets, by setting the role of the internal audit to achieve sustainable environmental leadership in the business environment by applying to some cement companies, With reference to the most important problems facing this important sector, which is represented in the role of internal audit in facing practices and activities to activate its role in improving the quality of environmental performance and then achieving environmental entrepreneurship. As a tool for collecting data from the study population, whose sample size was (385) individual employees, internal auditors, and auditors in the same company. The study concluded that the expressions of the independent variable “the role of internal auditing” among the company’s employees were of a medium degree, and the order of the dimensions of the survey form in terms of the dependent variable “sustainable environmental leadership”, with the degree of average availability, and the results of the study confirmed the existence of a direct correlation between the role of internal audit I have the company’s employees and auditors to achieve sustainable environmental leadership from their point of view, and the study recommended the necessity of establishments’ keenness to organize educational events and interest in establishing centers specialized in entrepreneurship.
Keywords: التنمية المستدامة -- الأداء البيئي -- شركات الأسمنت -- ريادة الأعمال -- التميز الإبداعي